PENGARUH BAURAN PEMASARAN JASA TERHADAP KEPUASAN WISATAWAN JAWA TIMUR PARK II KOTA BATU - Sari, Fitri Wulan; anto, Subi (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The development of tourism today is very fast and provide opportunity for national and regional economic growth. For the development of tourism and the government has continued to be driven belief that tourism can become the leading sectors replace oil and natural gas that has been the foundation of the government in supporting the state revenue. To that end, various regions in Indonesia are competing to develop the tourism sector in order to raise revenues. Marketing concepts evolve with the needs of the community. One of the primary needs to be taken by the manufacturer is the need for services. In marketing activities, important thing to note is how the providers of such services marketing mix that attention can then measure the satisfaction of its customers.Keywords: Product, Price, Place, Promotion, Physical Evidence, People, Process, Tourist Satisfaction